2001
DOI: 10.1063/1.1349090
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of the symmetry forbidden bending mode in molecular photoionization

Abstract: We present results on the energy dependence of the vibrational branching ratio for the bending mode in CO 2 3 u Ϫ1 photoionization. Specifically, we determine the v ϩ ϭ(0,1,0)/v ϩ ϭ(0,0,0) intensity ratio by detecting dispersed fluorescence from the electronically excited photoions. The results exhibit large deviations over a very wide energy range, 18Ͻh exc Ͻ190 eV. Production of the v ϩ ϭ(0,1,0) level of the ion from the v 0 ϭ(0,0,0) ground state is forbidden by symmetry, and while observations of such featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
1
11
1
Order By: Relevance
“…Specifically, we measure the response of the resonance to changes in alternative stretching vibrations, and the results display a striking mode-specific sensitivity to the antisymmetric stretching motion, which is a symmetry-forbidden excitation within the Franck-Condon framework. In recent CO 2 (C 2 g ) photoelectron studies, it has been shown that symmetry-forbidden vibrations can be induced by resonant variations of dipole amplitudes with changes in molecular geometry [8,9]. However, the current result is different from those previous investigations (indeed, as well as from all previous studies) in two significant ways.…”
contrasting
confidence: 98%
See 3 more Smart Citations
“…Specifically, we measure the response of the resonance to changes in alternative stretching vibrations, and the results display a striking mode-specific sensitivity to the antisymmetric stretching motion, which is a symmetry-forbidden excitation within the Franck-Condon framework. In recent CO 2 (C 2 g ) photoelectron studies, it has been shown that symmetry-forbidden vibrations can be induced by resonant variations of dipole amplitudes with changes in molecular geometry [8,9]. However, the current result is different from those previous investigations (indeed, as well as from all previous studies) in two significant ways.…”
contrasting
confidence: 98%
“…If one does not invoke the Franck-Condon approximation, then there is a possibility of single quantum excitations of nonsymmetric modes. In our CO 2 studies, we have found that resonantly amplified vibronic symmetry breaking arises naturally from the dependence of the photoionization scattering amplitudes on changes of the molecular geometry that occur during zero-point vibrational motions [8,9]. The same methods are well suited for calculating the effects observed here.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The experimental method has been described elsewhere 34,36,62 and only details pertinent to the present study are discussed here. A schematic of the apparatus is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%